The Mediation Role of Job Satisfaction in the Relationship between Career Development and Work Stress on Employee Loyalty: Case Study at BPR Agung Sejahtera - Wahyu Arif Hardianto; Hertiana Ikasari (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study aims to analyze and test the mediating role of job satisfaction in the relationship between career development and job stress on employee loyalty at BPR Agung Sejahtera. This study used a quantitative methodology to collect primary data from 90 employees of BPR Agung Sejahtera through questionnaires. Partial Least Squares (PLS) with Structural Equation Modeling (SEM) was used to test the relationship between latent variables. Data testing included validity, reliability, bootstrapping , Adjusted R-Square, Path Coefficient, and Specific Indirect Effects . The results showed that career development had a positive and significant effect on job satisfaction. Conversely, job stress was found to have a negative and significant effect on job satisfaction. Career development also had a positive and significant effect on employee loyalty. Job stress had a negative and significant effect on employee loyalty. Job satisfaction had a positive and significant effect on employee loyalty. However, the mediating role of job satisfaction in the relationship between career development and job stress on employee loyalty proved to be insignificant. This finding indicates that employee loyalty is more influenced by good career development and low levels of job stress than the mediating role of job satisfaction. Overall, these findings conclude that managing career development and work stress through job satisfaction is crucial for increasing employee loyalty. It is hoped that these research findings will help BPR Agung Sejahtera's management better manage its human resources to achieve the company's goals.